Signage as a Spatial Wayfinding Element: The Impact on User Circulation at M Bloc Space - Nesya Azhalia; Mona Anggiani (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
This study explores the impact of wayfinding systems on visitor activity distribution at M Bloc Space, located in South Jakarta. M Bloc Space is a creative area that is the result of revitalization, combining retail, culinary, community space, and performance functions in one semi-open area. The complexity of these functions requires an efficient wayfinding system. During M Bloc Design Week, wayfinding is predominantly supported by temporary signage to guide visitors through the event area. The method used in this study is a descriptive qualitative approach involving field observations and visual documentation to analyze various wayfinding elements such as signs, circulation, and visual orientation. The findings show that sign design, the presence of visual landmarks, and the legibility of circulation paths significantly impacts visitor movement patterns and activity distribution. Areas with clear visual orientation and consistent directional cues tend to have more visitors and support active social interaction. this research makes a contribution to the planning of commercial public spaces, so that they are more responsive to the navigation needs of users, while also improving the comfort and experience of spaces in urban creative areas such as M Bloc Space.